Social Support Build Resilience in Multidrug-Resistant Tuberculosis Patients: A Cross-Sectional Study in MDR-TB Patient Support Group - Akbar, Putri Wulan; Rachma, Lailia Nur; Rahmah, Zainabur; Firdaus, Muhammad Iqbal; Nanggali, Bryka Vian (The Avicenna Medical Journal, 2024)
Background: Multidrug-resistant tuberculosis (MDR-TB) patient faces multi-dimensional challenges due to the physical factor, long-term treatment, negative stigma, and psychosocial challenge. Addressing these issues patient requires a resilience. The formation of resilience is influenced by both internal and external factors, including social support. This study purposed to assess the social support impact on resilience in MDR-TB patients. Methods: This study was an observational analytic study with cross sectional design. A total of 33 respondents with MDR-TB confirmed, a member of MDR-TB support group, and under treatment were involved. The social support level was measured using the ISEL-12 (Interpersonal Support Evaluation List) questionnaire, while the level of resilience was assessed using the CD-RISC-25 (Connor-Davidson Resilience Scale). Spearman correlation test in SPSS Ver 24.0 was used to examine the relationship between social support and resilience among patients with MDR-TB. Results: Majority of respondents (17 respondents, 51.6%) have good social support and 23 respondents (69.7%) exhibited a good level of resilience. The Spearman correlation test revealed a significant positive correlation between social support and resilience, with a p-value of 0.030 and a moderate strength correlation coefficient (r) of 0.378. Conclusion: This finding showed that good social support toward MDR-TB patients gives positive impact to patients’ resilience. Thus strengthens the system of social support in support group is important to decrease the psychosocial challenges and help to succeed the treatment.